Evaluation of consumer reheating methods for destruction of Listeria monocytogenes in frankfurters - Ortega, M.T.; Thippareddi, H.; Phebus, Randall K.; Marsden, James L.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The USDA Food Safety and Inspection Service has issued a “zero tolerance” for Listeria monocytogenes in ready-to-eat meat and poultry products. The Food Safety and Inspection Service recommends that consumers “Reheat [hotdogs] until steaming” to reduce the risk of listeriosis. We evaluated L. monocytogenes survival on inoculated frankfurters after reheating using common, in-home consumer practices. Frankfurters were inoculated with a six-strain mixture of L. monocytogenes to an initial level of approximately 107 colony forming units (CFU)/gram. Eight inoculated franks for each treatment were cooked using boiling water, a conventional electric oven, or a microwave oven. L. monocytogenes recovery was calculated after plating on Modified Oxford Agar and Tryptose Phosphate Agar. L. monocytogenes reductions were 3.2 log10 CFU/gram on franks microwaved with or without water for 60 seconds or cooked in a conventional electric oven at 500°F for 2 or 5 minutes. Franks cooked in boiling water for 30 and 60 seconds achieved reductions of 4.3 and 4.9 log10 CFU/gram, respectively. Franks wrapped in a paper napkin and microwaved for 60 seconds resulted in a 6.8 log10 CFU/gram reduction, the most effective consumer reheating protocol.
Keywords: Beef; Listeria monocytogenes; Frankfurters; Reheating